The Experimental Tendency of Character in Contemporary Algerian Arabic Fiction: *What the Day Owes the Night* by Yasmina Khadra as a Model - Bouali, Walid; rachedi, hassane (El Omda in Linguistics and Discourse Analysis, 2022)
The novel is considered the most flexible literary genre, constantly open to transgression and transformation. This is why the Algerian novel has embraced multiple forms drawn from various literary genres, allowing it to enter the phase of modernity and the adventure of experimentation—entailing تجاوز، انزياح، and the breaking of established and conventional narrative patterns. Experimentation has thus affected all the artistic components of the novel, including the character, which plays a central role in driving events. The character has taken on diverse manifestations, been presented in new forms, and acquired different dimensions. Among Algerian novelists who have pursued experimentation in search of new artistic forms capable of addressing contemporary issues is the writer Yasmina Khadra, whose novel What the Day Owes the Night constitutes the focus of our study, through which we highlight the experimental tendency of character representation.